Exploration of the relationship between primary dysmenorrhea, pain perception, and menstruation-related quality of life in young women: a cross-sectional observational study - Rebeca Del Prado; María García-Arrabé; Ángel González-de-la-Flor; Marta De La Plaza San Frutos; Jaime Almazán Polo; Fabien Guérineau; Cecilia Estrada-Barranco (Frontiers in Global Women's Health)
BackgroundThis study explores the relationship between primary dysmenorrhea (PD), pain, pain catastrophizing, and menstruation-related quality of life in young women.MethodsA cross-sectional study was conducted involving 44 young women, both with and without PD. Various variables including pain intensity, pain catastrophizing, and menstruation-related quality of life were assessed using validated questionnaires. Correlation and regression analyses were performed to examine the relationships between the variables.ResultsSignificant associations were found between the presence of PD, tendency to catastrophize pain, and decreased menstruation-related quality of life. A high correlation was observed between pain intensity and catastrophizing, indicating mutual influence between these variables. Menstruation-related quality of life was affected in terms of health perception, psychological aspect, and symptoms among women with PD. The linear regression model demonstrated that catastrophizing explained 42.8% of the variance in menstruation-related quality of life.ConclusionsThese findings underscore the importance of addressing dysmenorrhea in young women, as it significantly impacts their quality of life related to menstruation. Understanding the factors contributing to dysmenorrhea and its effects on quality of life can inform more effective, patient-centered treatment strategies.